Prioritising investments in safety measures in the chemical industry by using the Analytic Hierarchy Process. (June 2020) - Abrahamsen, Eirik Bjorheim; Milazzo, Maria Francesca; Selvik, Jon T.; Asche, Frank; Abrahamsen, Håkon Bjorheim
Highlights: This article discusses the appropriateness of using the AHP in the chemical industry. We conclude that AHP is not in general adequate for use. First, uncertainty is not properly taken into consideration. Second, little weight is given to the strength of knowledge. We argue for some adjustments in the AHP. Abstract: In this paper we review and discuss the use of Analytic Hierarchy Process as a basis for prioritising investments in safety measures in the chemical industry. We point out that such a framework is not, in general, adequate. First, uncertainty is not properly taken into consideration because the focus is on expected values. Second, little weight is given to the strength of additional knowledge. In this paper we recommend some adjustments to a traditional Analytic Hierarchy Process in order to better guide safety investments. The chemical industry is the starting point, but the discussions are to a large extent general.